1997
DOI: 10.1074/jbc.272.37.23265
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Influence on the Kinetics of Ligand Binding to Acetylcholinesterase

Abstract: To explore the role that surface and active center charges play in electrostatic attraction of ligands to the active center gorge of acetylcholinesterase (AChE), and the influence of charge on the reactive orientation of the ligand, we have studied the kinetics of association of cationic and neutral ligands with the active center and peripheral site of AChE. Electrostatic influences were reduced by sequential mutations of six surface anionic residues outside of the active center gorge (Glu-84, Glu-91, Asp-280,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
248
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 210 publications
(268 citation statements)
references
References 44 publications
19
248
0
1
Order By: Relevance
“…The directed passage of ligand toward the active site, as suggested by some of these models, enhances the rate of diffusion-controlled reactions even further. Some models suggest that the electrostatic field experienced by the ligand on the surface of protein may guide it toward the active site [14][15]. Some other models present the van der Waals interactions as the prominent force directing the ligand over the protein surfaces [10].…”
Section: Resultsmentioning
confidence: 99%
“…The directed passage of ligand toward the active site, as suggested by some of these models, enhances the rate of diffusion-controlled reactions even further. Some models suggest that the electrostatic field experienced by the ligand on the surface of protein may guide it toward the active site [14][15]. Some other models present the van der Waals interactions as the prominent force directing the ligand over the protein surfaces [10].…”
Section: Resultsmentioning
confidence: 99%
“…For example, by using Brownian dynamics (BD) simulations (Ermak and McCammon, 1978;Northrup et al, 1984) (Sec. IV.F) to calculate diffusional association rates, Gabdoulline and Wade demonstrated that, for fast-associating protein pairs, electrostatic interactions enhance association and are the dominant forces determining the rate of diffusional association (Radic et al, 1997;Gabdoulline and Wade, 2001). Using related methods, Sept et al demonstrated the role of electrostatic interactions in determining the rates and polarity of actin polymerization (Sept et al, 1999;Sept and McCammon, 2001).…”
Section: Iib Biomolecule-ligand and -Biomolecule Interactionsmentioning
confidence: 99%
“…The binding affinities, from an electrostatic point of view, are determined by balance of these two energetic contributions (Xu et al, 1997;Lee and Tidor, 2001;Sheinerman and Honig, 2002;Russell et al, 2004;del Álamo and Mateu, 2005). Systematic studies of protein pairs, such as barnase and barstar Fersht, 1993, 1995;Frisch et al, 1997;Dong et al, 2003), and fasciculin-2 (Radic et al, 1997), as well as protein kinase A and balanol (Wong et al, 2001), have shown that charged and polar residues at the protein-protein interfaces play important roles in binding energetics. Similarly, Sept et al have demonstrated an important role for electrostatics in determining microtubule structure and stability (Sept et al, 2003).…”
Section: Iib Biomolecule-ligand and -Biomolecule Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparate salt effects on k a and k d are observed on many protein-protein pairs. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The binding of U1A with U1SLII shows exactly this salt behavior 7,14 and is thus expected to be modeled by a transient complex close to the native complex.…”
Section: Introductionmentioning
confidence: 99%